Frontal eye field in prosimian galagos: Intracortical microstimulation and tracing studies. Issue 4 (26th November 2017) - Stepniewska, Iwona; Pouget, Pierre; Kaas, Jon H.
Abstract: The frontal eye field (FEF) in prosimian primates was identified as a small cortical region, above and anterior to the anterior frontal sulcus, from which saccadic eye movements were evoked with electrical stimulation. Tracer injections revealed FEF connections with cortical and subcortical structures participating in higher order visual processing. Ipsilateral cortical connections were the densest with adjoining parts of the dorsal premotor and prefrontal cortex (PFC). Label in a region corresponding to supplementary eye field (SEF) of other primates, suggests the existence of SEF in galagos. Other connections were with ventral premotor cortex (PMV), the caudal half of posterior parietal cortex, cingulate cortex, visual areas within the superior temporal sulcus, and inferotemporal cortex. Callosal connections were mostly with the region of the FEF of another hemisphere, SEF, PFC, and PMV. Most subcortical connections were ipsilateral, but some were bilateral. Dense bilateral connections were to caudate nuclei. Densest reciprocal ipsilateral connections were with the paralamellar portion of mediodorsal nucleus, intralaminar nuclei and magnocellular portion of ventral anterior nucleus. Other FEF connections were with the claustrum, reticular nucleus, zona incerta, lateral posterior and medial pulvinar nuclei, nucleus limitans, pretectal area, nucleus of Darkschewitsch, mesencephalic and pontine reticular formation and pontine nuclei. Surprisingly, the superior colliculus (SC) contained only sparse anterograde label. Although most FEF connections in galagos are similar to those in monkeys, the FEF‐SC connections appear to be much less. This suggests that a major contribution of the FEF to visuomotor functions of SC emerged with the evolution of anthropoid primates. Abstract : Frontal eye fields (FEF) in galagos connect to cortical and subcortical structures participating in higher order visual processing. Most connections are similar to those in monkeys, however FEF‐superior colliculus projections are sparse, suggesting that major contributions of FEF to visuomotor functions of SC emerged with the evolution of anthropoid primates.